Museologia e comunicação: um estudo do potencial museológico do Theatro da Paz - BRAGA, Bruno Braga (2019)
The goal of the current research was to have Theatro da Paz (the Opera House) investigated from the museology perspective, considering the musealization as a significant element that provides its preservation regarding the actions of communication, focusing on guided tours developed by the institution and the way they are understood, with regard to their possible process of musealization. The study has as its defense the fact that Theatro da Paz as an asset that has the potential to be musealized, with the purpose of fostering and intensifying its preservation, considering the expressiveness of its communication actions, highlighting the guided visits promoted by the Institution added to its set of works permanently found in space and presented to the public including the history of the place with the intent to communicate. The results obtained by this work were the proposal of musealization of the theater by means of a museological potentialities study evident in the guided visits considering elements of the communication that discuss museological questions, as well as the obtaining of data that could reveal approximations and distances of this cultural space to museum assets.